2019
DOI: 10.3389/fchem.2019.00566
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Perturbing Actions by Verteporfin, a Benzoporphyrin Photosensitizer, on Membrane Ionic Currents

Abstract: Verteporfin (VP), a benzoporphyrin derivative, has been clinically tailored as a photosensitizer and recently known to suppress YAP-TEAD complex accompanied by suppression of the growth in an array of neoplastic cells. However, the detailed information is little available regarding possible modifications of it and its related compounds on transmembrane ionic currents, despite its growing use in clinical settings. In this study, from whole cell recordings, VP (0.3–100 μM) increased the amplitude of Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(164 reference statements)
0
11
0
Order By: Relevance
“…GAL-021-mediated suppression of I K(Ca) observed in GH 3 cells was found to be attenuated by further application of either verteporfin or ionomycin, yet not by diazoxide, an activator of K ATP channels [51]. Vertiporfin was recently reported to activate BK Ca channels [35], while ionomycin is a Ca 2+ ionophore. In keeping with the present observations and previous studies [5,6], the inside-out current recordings revealed the effectiveness of GAL-021 in decreasing the open-state probability of BK Ca channels that would be open.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GAL-021-mediated suppression of I K(Ca) observed in GH 3 cells was found to be attenuated by further application of either verteporfin or ionomycin, yet not by diazoxide, an activator of K ATP channels [51]. Vertiporfin was recently reported to activate BK Ca channels [35], while ionomycin is a Ca 2+ ionophore. In keeping with the present observations and previous studies [5,6], the inside-out current recordings revealed the effectiveness of GAL-021 in decreasing the open-state probability of BK Ca channels that would be open.…”
Section: Discussionmentioning
confidence: 99%
“…After cells were left to adhere to the bottom for several minutes, the recordings were performed. Patch-clamp experiments under either whole-cell, cell-attached, or inside-out mode were achieved with either an RK-400 (Biologic, Claix, France) or an Axopatch-200B amplifier (Molecular Devices, Sunnyvale, CA) [16,35]. We fabricated patch pipettes, the resistance of which was around 3 to 5 MΩ, from Kimax-51 borosilicate capillaries (#34500; Kimble; Dogger, New Taipei City, Taiwan) pulled on either a PP-830 vertical puller (Narishige, Major Instruments, New Taipei City, Taiwan) or a P-97 programmable horizontal puller (Sutter Instruments, Novato, CA, USA), and the pipettes were then fire polished with an MF-83 microforge (Narishige).…”
Section: Electrophysiological Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tip resistance was in the range of 3-5 MΩ when the electrode was backfilled up with different internal solutions detailed above. Ion currents were measured in the whole-cell mode of standard patch-clamp technique by using either an Axopatch 200B (Molecular Devices, Sunnyvale, CA, USA) or an RK-400 (Bio-Logic, Claix, France) patch amplifier [15,27,47]. The recorded area on the vibration-free table was shielded by using a Faraday cage (Scitech, Seoul, South Korea) to minimize mechanical noise.…”
Section: Electrophysiological Measurementsmentioning
confidence: 99%